Observing and Modeling the Response of Placentia Bay to an Extratropical Cyclone - Guangjun Xu; Guoqi Han; Changming Dong; Jingsong Yang; Brad DeYoung (Atmosphere, 2019)
An extratropical cyclone reported to have the largest wind speed in Newfoundland in morethan a decade landed on the island of Newfoundland on 11 March 2017. The oceanic responses inPlacentia Bay on the southeast coast of Newfoundland to the winter storm were examined usingobserved data and the Finite-Volume Community Ocean Model (FVCOM). The peak non-tidal waterlevel increase, i.e., storm surge, reached 0.85mat St. Lawrence and 0.77mat Argentia on Placentia Bay.Sea surface temperature slightly decreased after the storm passage according to buoy and satellitemeasurements. Root mean square dierences (RMSD) of the magnitude of storm surge between modelresults and observations are 0.15 m. The model sea surface temperature showed a small decrease,consistent with observations, with RMSDs from 0.19 to 0.64 C at buoy stations. The simulatedsurface current changes agree with buoy observations, with model-observation velocity dierenceratios (VDR) of 0.75–0.88. It was found that, at Argentia (St. Lawrence), the peak storm surge inPlacentia Bay was dominantly (moderately) associated with the inverse barometric eect, and thesubsequent negative surge was mainly due to the wind eect at both stations. The sea surface coolingwas associated with oceanic heat loss. In the momentum balance, the Coriolis, pressure gradient,and advection terms were all important during the storm, while the first two terms were predominantbefore and after the storm.